Artifak Purba Pasemah: Analisis Ungkap Rupa Patung Megalitik di Pasemah - Erwan Suryanegara; Nuning Damayanti; Wiyoso Yudoseputro (Journal of Visual Art and Design, 2007)
Prehistoric relics, especially those of megalithic traditions, were found many in the plateau of Pasemah. From several types of megalithic artefacts, megalithic idols are the one that excessively found in Pasemah. Unfortunately, scientific information about these ancient artefacts in Pasemah is still scarcely to be found, especially in the form of visual data and reports. Based upon this notion, this research conducted a study to investigate, document and describes the existence, depiction, the object, expression style, symbol, and attribute of the megalithic idols of Pasemah; using the approach of ungkap rupa. The study discovers that the proponent society of megalithic culture in Pasemah had used and applied bronze. They had good ability in chiseling idols from big stones of andesit, formed it in sharp corners and created accurate forms. The depicted idols show that its form has a dynamic pictorial postures and shapes, although some are also made in the style of realistic expression. The idols are formed in a leaning forwards posture, its head or face tilted upward, and its feet usually visualized in the bended forms, depicting austronesoid man and animals complete with its attribute and symbols. Further, the study indicates that these megalithic idols were representations of symbolic-mystical beliefs of a Pasemah's society which were based on cosmology of the past. Accordingly, these idols were inseparable parts of Pasemah's ancestor veneration rituals. The distinctiveness of these idols is found in their dynamics"”both in pictorial and realistic depiction"” that seem to be the masterpiece of megalithic idols of Pasemah at that time. The idols visualize the complete body part of austronesoid man and/or animals (head, body, foot/feet, and hand), which indicates that the megalithic idols of Pasemah represents a mystical culture of a society that whorshiped the spirit of their ancestors, live as an agrarist society of farmer (peladang) system, and encourages the patriotic characteristic of man.